Critical perspectives for questioning research and social intervention today - Muñoz-Arce, Gianinna (Critical Proposals in Social Work, 2023)
It is with great joy that we deliver this fifth issue of our journal Propuestas Críticas en Trabajo Social - Critical proposals in Social Work, which we have dedicated to the discussion of research and social intervention approaches or perspectives. You will notice in the following pages that certain approaches that have emerged strongly in the discussions of the social sciences and humanities in recent times, are also reflected in the articles that make up this issue: feminisms, intersectional perspectives Intersectional perspectives, decolonial thought, anti-colonial and Indo-American proposals, and interpellations from feminism to Marxism, classical hermeneutics and evidence-based approaches. Various notions, such as "intellectuality", "evidence", "objectivity", "objectivity", and "intellectuality", "evidence", "objectivity", "professional training", "critical thinking", "critique", among others, will be subjected to an elaboration from perspectives not seen or traditionally little addressed in the past: some silenced -such as feminisms and de/anti-colonial proposals- and others simply not thought of before as a conceptual option -such as the opening of elites as a field of study or the understanding of non-hegemonic motherhood as a key to social intervention.